Ion mobility-mass spectrometry reveals long-lived, unfolded intermediates in the dissociation of protein complexes. - Ruotolo, B; Hyung, S; Robinson, P; Giles, K; Bateman, R; Robinson, C (2007)
Folded or not? Ion mobility-mass spectrometry investigation of an activated macromolecular protein complex lends insight into the structures of intermediates formed in the dissociation process. The activated ions of human tetrameric transthyretin populate partially folded intermediate states (see picture; folded subunits in blue, partially unfolded subunits in red) prior to dissociation. (Figure Presented). © 2007 Wiley-VCH Verlag GmbH and Co. KGaA.